Stereochemistry of organic compound : Principles and applications - Nasipuri, D. (New Delhi: New Age International, 2011)
During recent years, stereochemistry has undergone a phenomenal growth both in theory and practice, with a concomitant increase of interest among the organic chemists, biological chemists, medicinal chemists, and pharmacologists. The present text provides an up-to-date, coherent; and comprehensive account of the subject starting from the fundamentals and leading up to the latest developments as far as practicable. Emphasis has been placed on symmetry-based approach to molecular chirality, stereochemical terminologies (modern stereochemistry is replete, with them), topicity and prostereoisomerism, conformational analysis, dynamic stereochemistry, chiroptical properties, and assignment of absolute configuration to chiral molecules. Dynamic stereochemistry has been discussed with reference to conformation-reactivity correlation, stereoselective syntheses, and pericyclic reactions. A large cross-section of organic reactions with stereochemical implication has been incorporated. Attempts have been made to familiarise the readers with modem instrumental techniques, nuclear magnetic resonance in particular, used for stereochemical investigation. Each chapter is provided with a summary which highlights the main points of the text. Selective references, mostly of textbooks, monographs, review articles, and significant original papers have been given extending sometimes to early 1991.The book is expected to fulfil the long-felt need for a comprehensive text on modern organic stereochemistry which is conspicuously absent since the publication of Professor Eliels book in 1962. The text may be adopted at any stage of the university teaching and at the same time be useful to the practising organic chemists.
Include bibliographical references; Index 521-537p.
Keywords: Molecular recognition; Organic chemistry; Stereochemistry; Chemistry